CERTIFICAÇÃO FLORESTAL NO BRASIL UMA FERRAMENTA EFICAZ PARA A CONSERVAÇÃO DAS FLORESTAS NATURAIS? - Spathelf, Peter; de Mattos, Patricia Povoa; Botosso, Paulo César (Floresta, 2004)
A certificação florestal é descrita como instrumento de mercado para apoiar um manejo florestal sustentável. Um foco especial é dado pela certificação sob FSC, mas também pelo sistema esquema nacional de certificação florestal no Brasil, o CERFLOR. O que se questiona é se a certificação poderá contribuir com a adoção de práticas de bom manejo pela motivação devido às vantagens advindas da certificação ou pela conscientização do consumidor. As principais forças motrizes do desmatamento nas florestas brasileiras ainda existem, por isso a contribuição da certificação para a conservação das florestas naturais parece ser limitada. FOREST CERTIFICATION IN BRAZIL AN EFFICIENT TOOL FOR THE CONSERVATION OF NATURAL FORESTS? Abstract Forest certification is described as a market-oriented tool to support sustainable forest management. Special emphasis is given to forest certification under FSC, but also to the national certification scheme in Brazil, CERFLOR. The key question is, whether forest certification gives a significant contribution to reduce deforestation and conventional unsustainable logging, respectively under the circumstances of the Brazilian forest sector and domestic consumer behaviour. The main driving forces for deforestation in Brazil still exist and, consequently, the impact of forest certification for the conservation of natural tropical forests in Brazil is still seen to be limited.